STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PADA UMKM KERIPIK PISANG KEPOK - Humaira Dhiya WIjayanti; Agnia Melani; Shafa Azkia Ramadhan (Media Resonansi Pengabdian Masyarakat, 2025)
Digital Marketing is marketing carried out through digital media, mobile devices, and other digital media platforms. The purpose of this activity is to find out how to use digital marketing techniques to increase sales figures and expand the market for Kepok banana chips. This activity wants to find out the sales strategy in digital marketing in Kepok banana chips MSMEs by identifying marketing strategies and analyzing product SWOT. The use of SWOT aims to understand the strengths, weaknesses, opportunities, and threats of the Company. This increasingly rapid economic development will have an impact on company competition and business actors utilize information technology to develop and promote the Company's products. Kepok banana chips conduct sales and marketing through social media which plays an important role in increasing sales and consumer interest. Data sources were obtained through interviews and documentation. The results of the activities found show how the digital marketing strategy is carried out by Kepok banana chips, this research method uses a qualitative method.Keywords: Digital Marketing, social media, Kepok banana chips